Opportunities for Improving the Inventory Management Based on the Example of Albanian Manufacturing Companies - CANCO, Irina (Socialiniai tyrimai, 2022)
In the way of fast and complex developments of businesses, the inventory plays as well an important role. The complexity of the economic environment where the businesses operate and the problems they encounter orient the manager’s attention towards the management of inventory. This refers to the inventory’s specifics in general and his constituent elements. Despite these the common characteristic of the inventory is its double character, as on one hand it represents necessary, inevitable elements for the development of the productive activity of every business, and on the other the inventory requires considerable commitments of the financial sources. This has made the efficient management of the inventory a central problem, on which a series of researches have been concentrated.This paper is an effort to deal with some problems of efficient management of the inventory in the business organizations, regarding the quantity, quality, and time dimensions on the inventory because inventories are the focal point in business performance. But, the greatest part of businesses in Albania operate in the conditions when information about inventory management missing. Problems addressed in this paper can be serve the managers for improvement their job in the future.